Psychosocial Dimensions Of Beedi Work: Mapping The Invisible Pressures On Women Workers - Karunya Gunavathy K, N. Manikandan (Journal of Informatics Education and Research, 2025)
Background: This systematic literature review explores the transitions of women beedi workers from informal tobacco-based labor to sustainable livelihoods through social entrepreneurship. Methods: The review followed PRISMA guidelines and included peer-reviewed studies, government reports, and NGO publications from 2000–2024. Results: Findings show limited research on ecosystem-level support, digital enablement, psychological barriers, and regional comparative transitions. Conclusions: Significant gaps remain in designing scalable, evidence-based livelihood transition models for women beedi workers.